Revitalisasi Implementasi Kurikulum Pendidikan - Fahmi, Fauzi; Bitasari, Wahyu (Al-Fikru: Jurnal Ilmiah, 2020)
This study aims to analyze the revitalization of curriculum implementation in formal educational institutions. This research uses qualitative research methods based on literature study. Sources of data used in this study are various government policies related to the education curriculum in Indonesia, especially government policies concerning the 2013 curriculum. Data analysis was carried out by analyzing descriptive analytic data. The results of this study indicate that: 1) curriculum implementation includes: a) program development, b) learning implementation, and c) evaluation. 2) Preparation from teachers and school authorities, namely: a) Readiness of material can be in the form of readiness such as curriculum tools, school infrastructure, financial elements, and elements of the school environment. b) Non-material readiness can be in the form of reliable and professional educational staff (principals/ teachers), readiness of employees and readiness of elements of students and parents of students.